دراسة تحليلية لحالات التنظير القصبي للمرضى المراجعين لمشفى الأسد باللاذقية خلال عام 2016 - حلوم, رمزه (Latakia University Journal -Medical Sciences Series, 2018)
خلال سنة 2016 قمنا بإجراء 167 تنظيرا قصبياً استقصائياً ( 101 ذكور – 66 أنثى ) وأجريت بمنظار ليفي مرن ماركة pentax قطر رفيع slim , وتم تحضير المرضى للتنظير بالتخدير الموضعي للأنف والبلعوم والحنجرة بالليدوكائين . وفي حالات قليلة وخاصة تم التركين الوريدي بالـ Midazolam 5مغ. وكان تحمل التنظير جيداً ولم تحدث اختلاطات تستدعي الاستشفاء. كانت استطبابات التنظير هي: - الاشتباه بالخباثة حيث تم تشخيص 49 حالة بنسبة 56,3% وشخصت وعزلت الإمراضيات في حال الاشتباه بالأخماج عند 11 مريض بنسبة 45,8% وتم تشخيص السل لدى 9 مرضى بنسبة 42,8% من الحالات المشتبهة. - وفي حالات نفث الدم: تم تحديد موقع النزف ومعرفة العامل المسبب لدى 12 مريض بنسبة 63%. - وفي حالات السعال المزمن تم تأكيد التشخيص لدى 4 مرضى بنسبة 50% - وفي حالات الآفات الرئوية الخلالية تم تشخيص 4 مرضى بنسبة 50% ونؤكد بعد الدراسة على أهمية التنظير القصبي كوسيلة استقصائية تشخيصية وخاصة في حالات الخباثة , وعند سلبية الفحوصات الأخرى : دم , قشع عند الشبهة بالأخماج والسل وفي حالات نفث الدم والإمراضياتالخلالية وخاصةً أنه إجراء خارجي جيد التحمل واختلاطاته نادرة. During 2016 we have made 167 survey bronchoscopy (101 males & 66 females),they had been done by flexible fibroscope (pentaxTM) slim diameter . Patients has prepared for the endoscopy by local anesthesia on nose ,pharynx and larynx using Lidocaine .In few particular cases , the sedation has been done by Midazolam (5mg) intravenous . The endoscopy's tolerance was good and no complication that require recovery occurred . The indications of the endoscopy were suspected malignancy, 49 cases had diagnosed in the rate of 56.3%. The disorders had been diagnosed and isolated in the case of suspected infections in 11 patients in the rate of 45.8%.The tuberculosis had been diagnosed in 9 patients in the rate of 42.8%. In hemoptysis cases ,bleeding site and causing factor had causing factor had been detected in 12 patients in rate of 63%. In chronic cough cases, the diagnosis had been confirmed in 4 patients in the rate of 50%. In case of interstitial pulmonary lesions , the diagnosis had been confirmed in 4 patients in the rate of 50%. After the study ,we emphasize the importance of broncoscopy as survey diagnostic instrument especially in malignancy cases , other negative tests (blood, sputum ), suspected infections , tuberculosis ,hemoptysis cases and interstitial lesions .Especially it is external good tolerances procedure with rare complication.